2005
DOI: 10.1021/es050574+
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hydroxylated Polybrominated Diphenyl Ether Metabolites in Blood Plasma from Polybrominated Diphenyl Ether Exposed Rats

Abstract: Polybrominated diphenyl ethers (PBDEs) are ubiquitous environmental contaminants due to their use as flame retardants. Similarly to PCBs, the PBDEs are metabolized to hydroxylated metabolites (OH-PBDEs) in mammals. In the present study equimolar doses of seven environmentally relevant PBDE congeners were given intraperitoneally as a mixture to rats, and their blood plasma was analyzed for parent compounds and hydroxylated metabolites 1 and 5 days after dosing. Sixteen OH-PBDEs and two diOH-PBDEs were detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
143
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(152 citation statements)
references
References 42 publications
(58 reference statements)
8
143
1
Order By: Relevance
“…These orthosubstituted OH-PBDEs and MeO-PBDEs have been structurally identified and confirmed as natural compounds (Malmvarn et al, 2005(Malmvarn et al, , 2008. The meta-and para-substituted OH-PBDEs have been reported to be biotransformation products produced during PBDE exposure (Malmberg et al, 2005;Marsh et al, 2006;Qiu et al, 2007). Recently, Wan et al demonstrated the interconversion of OH-PBDE and MeO-PBDE in Japanese medaka (Wan et al, 2010).…”
Section: Introductionmentioning
confidence: 91%
“…These orthosubstituted OH-PBDEs and MeO-PBDEs have been structurally identified and confirmed as natural compounds (Malmvarn et al, 2005(Malmvarn et al, , 2008. The meta-and para-substituted OH-PBDEs have been reported to be biotransformation products produced during PBDE exposure (Malmberg et al, 2005;Marsh et al, 2006;Qiu et al, 2007). Recently, Wan et al demonstrated the interconversion of OH-PBDE and MeO-PBDE in Japanese medaka (Wan et al, 2010).…”
Section: Introductionmentioning
confidence: 91%
“…Several compounds, assigned to be mono-OH-PBDEs and di-OH-PBDEs were also detected, however, their structures could not be identified in the present study because of an absence of authentic standards. It is suggested that meta-methoxysubstituted PBDEs does not contain fragment ions of [MÀCH 3 (Malmberg et al, 2005;Marsh et al, 2004). Therefore, position of the hydroxylated group in the unidentified monohydroxylated PBDE congeners was suggested based on the characteristic fragmentation pattern of their EI mass spectra.…”
Section: Identification Of Target Compoundsmentioning
confidence: 99%
“…It was reported that OH-PBDE metabolites from laboratory studies in animals were dominated by hydroxyl groups in the meta or para positions (Malmberg et al, 2005;Marsh et al, 2006;Qiu et al, 2007). Ortho OH-substituted OH-PBDEs have been identified as naturally occurring formulations in marine organisms such as sponges, tunicates, and algae (Fu et al, 1995;Malmvarn et al, 2005;Unson et al, 1994).…”
Section: Levels and Patterns Of Oh-pbdes And Bpsmentioning
confidence: 99%
See 2 more Smart Citations